Binge Eating and Mindful Eating: Exploring the Mediating Role of Tri-Gunas of Personality - Himanshu Lokhande; Dr. Neeraj Panwar (International Journal of Indian Psychȯlogy, 2025)
Background: Abnormal eating behaviors such as binge eating are increasing, prompting interest in their psychological roots. Mindful eating provides a healthier alternative. This study uses the Triguna theory to examine how lifestyle, food habits, and personality traits are interconnected in adolescents. Aim: The current study aims to explore the mediating role of triguna personality between binge eating and mindful eating. Methods: This study involved 214 urban high school students (ages 15–20) from English-medium schools. Purposive sampling techniques were used. A correlational research design as a quantitative approach, was used to examine the association.  It aimed to investigate binge and mindful eating in relation to Triguna personality traits, examining the gunas’ mediating role between these eating behaviors. Tools were used Binge eating scale (BES; Gormally et al., 1982), Mindful eating questionnaire (Framson et al., 2009) and Vedic Personality Inventory (Wolf, 1999) Result and Conclusion: The findings indicated that binge eating behavior was positively associated with Tamas guna, reflecting traits such as inertia, impulsivity, and lack of self-regulation. In contrast, mindful eating was positively correlated with Sattva guna, which represents balance, awareness, and self-discipline. Mediation analysis confirmed that Triguna personality traits significantly influenced the relationship between binge and mindful eating. Specifically, higher tamasic tendencies predicted greater binge eating, while higher sattvic tendencies supported mindful eating behaviors. These results suggest that fostering sattvic qualities through interventions like mindfulness practices may help reduce maladaptive eating patterns in adolescents and promote better mental and physical health.